2019
DOI: 10.15557/jou.2019.0031
|View full text |Cite
|
Sign up to set email alerts
|

The role of TVT position in relation to the pubic symphysis in eliminating the symptoms of stress urinary incontinence and urethral funneling

Abstract: The introduction of suburethral sling was a breakthrough in the treatment of stress urinary incontinence in women. The method is highly effective. However, the mechanism of action of a sling and the reasons for surgical failures are not fully understood. Aim: The aim of the study was to assess the impact of sling-pubic symphysis distance on eliminating the symptoms of stress urinary incontinence and urethral funneling. Materials and methods: The analysis included 106 patients who reported 3 to 6 months after s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 18 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…Two of the most commonly used measures of MUS compression in the literature are: the pubic symphysis–tape gap [ 6 , 18 , 19 , 20 , 21 ] and the tape–urethral lumen distance [ 4 ]. Although we do not have a cut-off point to define SUI in the gap between the pubic symphysis–tape, we should mention that patients with SUI present a larger pubic symphysis–tape gap than continent patients [ 6 , 18 , 19 , 20 , 21 ]. Measurements of this gap for continent patients range from 10.9 mm to 20.3 mm, and for SUI patients from 13.3 mm to 26.1 mm [ 6 , 18 , 19 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Two of the most commonly used measures of MUS compression in the literature are: the pubic symphysis–tape gap [ 6 , 18 , 19 , 20 , 21 ] and the tape–urethral lumen distance [ 4 ]. Although we do not have a cut-off point to define SUI in the gap between the pubic symphysis–tape, we should mention that patients with SUI present a larger pubic symphysis–tape gap than continent patients [ 6 , 18 , 19 , 20 , 21 ]. Measurements of this gap for continent patients range from 10.9 mm to 20.3 mm, and for SUI patients from 13.3 mm to 26.1 mm [ 6 , 18 , 19 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although we do not have a cut-off point to define SUI in the gap between the pubic symphysis–tape, we should mention that patients with SUI present a larger pubic symphysis–tape gap than continent patients [ 6 , 18 , 19 , 20 , 21 ]. Measurements of this gap for continent patients range from 10.9 mm to 20.3 mm, and for SUI patients from 13.3 mm to 26.1 mm [ 6 , 18 , 19 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the position of the second sling, some recent studies have revealed that the success rate of repeated suburethral sling procedures was better for slings positioned at the proximal urethra (17). Meanwhile, urodynamic stress incontinence is more likely observed in women with a greater sling-pubis gap, and sling location should be close to the symphysis pubic to reduce the length of the urethral funneling (18,19). Additionally, various parameters were always detected in the literature concerning SUI evaluation, including the distance of sling to the urethra, sling angle, and location of the sling relative to mid-urethral or bladder neck (20,21).…”
Section: Discussionmentioning
confidence: 99%